Mixed Marketing Strategy On Coffee Consumer Satisfaction At Cafe De Tropodo Sidoarjo - Sri Tjondro Winarno; Dwi Wahyuningtyas; Dinariningrum Rahma Winarno (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2021)
Coffee is currently experiencing a rapid development. This condition is indicated by the existence of café or coffee shop in almost every location. It will create increasingly fierce competitions among coffee business owners, with various strategies that will be applied to win the competition. Mixed marketing is ​​one strategy that is often applied to run the business in order to win the competition. The mixed marketing is ​​a part of marketing that is used by a company so that the target can be achieved properly. The purpose of this study was to analyze the effect of mixed marketing strategy on coffee consumer satisfaction at Cafe De Tropodo Sidoarjo. The number of respondents in this study were 75 cafe visitors, who were selected by chance (accidental sampling), and the data obtained were analyzed using SEM PLS 6.0. The results showed that the 7 P's mixed marketing (product, price, place, promotion, people, physical evidence, and process) had a significant positive effect on coffee consumer satisfaction in Sidoarjo.